KONTEKSTUALISASI PENDIDIKAN ISLAM PERSPEKTIF ULUL ALBAB DALAM ERA LITERASI DIGITAL - Devy Habibi Muhammad; Reza Hilmy Luayyin (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2022)
This article examines the contextualization of Islamic education perspective ulul albab in the era of digital literacy. Ulul Albab education that transforms Islamic values. So that these values can have a function and can develop in society. This research is carried out by looking for research information and data in books, scientific journals, and publication references in the library. The library material in question is works related to Islamic education and ulul albab. The figure of the next generation of the nation is a person who is intellectual and has an understanding of the verses of God, and makes this nature used as a field of science for the humane kususnya believers who always remember God in In any situation, digital literacy in the concept of ulul albab education is an effort to improve digital literacy for the provision of life in the world. Ulul Albab education is a mainstream that can lead to changes in education so that it can develop ideas and solve problems that occur about religion, social and politics. Ulul Albab education is aimed at how to guide and direct children potentially and have competence so that they can be actualized, and emphasize the intellectual and moral aspects of good morals and child development such as spiritual, scientific, intellectual, physical, language. The ultimate goal of this education lies in the realization of devotion to God.